Fiscal multipliers of central, state and local government and of the social security funds in Germany: Evidence of a SVAR - Josef Hollmayr; Jan Kuckuck (Deutsche Bundesbank, 2018)
By applying a Structural Vector Autoregressive (SVAR) approach this paper estimates the effects of fiscal policy shocks of different government sub-sectors on aggregate GDP in Germany. From a general government perspective, the results show that besides investment, it is particularly changes in social contributions that yield significant output effects. The GDP response to fiscal policy shocks of the various government sub-sectors turns out to be very heterogeneous. Investment expenditures at all public authorities (central, state and local) trigger positive and statistically significant output effects at least on impact. By contrast, it is only government consumption at state government level and monetary benefits at state government and social security level that induce statistically significant and positive effects on economic activity. Overall, the disaggregated results suggest that besides investment, it is chiefly expenditure with a large share of personnel-related outlays that can have positive effects on aggregate output.
Keywords: H71; H5; H30; 330; Fiscal Policy; Multipliers; VAR; Disaggregated Government Levels and Instruments